Logic and humour in the fabliaux : an essay in applied narratology - Pearcy, Roy (Gallica (Woodbridge (Suffolk, England)), 2007)
A theoretically defensible inventory of the fabliaux based on a new structural definition. In response to Bédier's description of the fabliaux as 'funny stories in verse', Roy Pearcy suggests a new structural definition, permitting the creation of a theoretically defensible inventory, which includes and augments the texts admitted by Per Nykrog and discards numerous stories already challenged for authenticity. Joseph Bédier's 1893 definition of the fabliaux as 'funny stories in verse' is still widely accepted as the best brief and general description for a heterogeneous collection of texts. But the heterogeneity creates difficulties and at the periphery of the canon all three of the criteria included in Bédier's definition are open to question. The inventory proposed in the current study is based on a new structural definition, a 'conjointure', akin to that of romance, combining a logical 'episteme' with a rhetorical 'narreme'. The 'episteme' features a contradictory taken from Boolean algebra, and assumes four different forms, depending on whether ambiguity resulting from the contradictory is understood by neither, by both, or by either the sender or the receiver of a message, In the first two instances, a character foreign to the episteme intervenes to resolve confusion in the narreme, or appears as the victim of the sophistical assumption of a contrary-to-fact reality; in the latter instances the sender or the receiver of the message in the episteme triumphs in the narreme. The resulting inventory, including and augmenting the texts admitted by Per Nykrog and discarding numerous stories already challenged for authenticity, is theoretically defensible to a degree not previously achieved. ROY PEARCY is an Honorary Research Fellow of the University of London.